2020
DOI: 10.1186/s42826-020-00057-x
|View full text |Cite
|
Sign up to set email alerts
|

Brain Factor-7® improves learning and memory deficits and attenuates ischemic brain damage by reduction of ROS generation in stroke in vivo and in vitro

Abstract: Brain Factor-7® (BF-7), silk fibroin peptide, is known to be effective in improvement of memory and learning ability. In this study, the effects of BF-7 (10 mg/kg, p.o., pre-treatment for 7 days and post-treatment for 7 days) on neuroprotection and memory and learning functions were investigated in a rat model of transient focal cerebral ischemia and a gerbil model of transient global forebrain ischemia. Furthermore, to find the mechanism of BF-7, we examined the neuroprotective and antioxidative effects of BF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…In this study, the activated number of astrocytes and microglia FMA-pretreated groups were significantly decreased in the CA1 area. In previous studies, the same pattern of glial cell activation after TI induction was observed [ 28 , 35 ]. These results indicated that FMA extract has neuroprotective effects against TI insults that reduce gliosis.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In this study, the activated number of astrocytes and microglia FMA-pretreated groups were significantly decreased in the CA1 area. In previous studies, the same pattern of glial cell activation after TI induction was observed [ 28 , 35 ]. These results indicated that FMA extract has neuroprotective effects against TI insults that reduce gliosis.…”
Section: Discussionsupporting
confidence: 79%
“…TI in gerbils for 5–15 min induced neuronal cell death in the hippocampal CA1 area that was easily distinguished based on CV staining, immunohistochemistry, and F-J B histofluorescence [ 27 – 29 ]. In addition, F-J B is an effective marker for investigating neuronal degeneration in the brain following ischemic insults due to its strong affinity for degenerating neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular ROS production was assessed by DCF-DA staining as previously described [ 59 ]. In brief, cells were pre-treated with or without 10 μM spermidine, 5 mM NAC, or 5 μM BAPTA-AM for 1 h before incubation with 300 μM H 2 O 2 for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…These data indicate that REG3A could be mediating early leukocyte chemotaxis to the site of infarct. CX3CL1, MBL2, F7, CSF‐1, and IL13 have been reported to perform neuroprotective functions in stroke (Hu et al, 2020; Kolosowska et al, 2019; Limatola & Ransohoff, 2014; Noh et al, 2020; Osthoff et al, 2011). Together, these data show the complexity of REG3A involvement in the immune/inflammatory molecular signaling initiated by ischemic stroke.…”
Section: Resultsmentioning
confidence: 99%